Nails or Knots: How Was Jesus Crucified? - Arroyo García, Jeffrey P. (The Biblical archaeology review, 2025)
Although crucifixion was a common form of punishment in the Roman world, archaeology has provided few clues as to how the brutal practice was performed. And although the Gospel accounts use vague terminology when describing Jesus’s execution, a longstanding Christian tradition assumes bodies were nailed to the cross. Close inspection of the historical evidence, however, indicates that nailing was probably introduced only after Jesus’s time.